The market makers how retailers are reshaping the global economy - Hamilton, Gary G.; Petrovic, Misha; Senauer, Benjamin (Oxford : Oxford University Press, 2011)
In 11 chapters by leading scholars, 'The Market Makers' provides a detailed but highly readable analysis of how retailers have become the leading drivers of the new global economy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Retail trade; International trade; International business enterprises; Globalization -- Economic aspects